Strategic international marketing : an advanced perspective - Melewar, T. C.; Gupta, Suraksha (Houndmills, Basingstoke, Hampshire ; New York : Palgrave Macmillan, 2012)
Strategic International Marketing collates the most recent ideas, trends and original research in the theory and practice of global marketing strategy and tactics. Straightforward language and illustrative case studies feature throughout this text from the leading thinkers in the international marketing field
Includes index
BSBA
Keywords: Export marketing; International business enterprises